Determinan perilaku menabung dari Mahasiswa di NTT: Peran kontrol diri sebagai variabel intervening - Lejap, Hedwigh Hendrikus Temai; Wutun, Maria B. M. G.; Manafe, Henny A.; Bau Mau, Ignatia B. (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
The main objectives of this study were to determine the level of financial literacy, family financial socialization, peers, self-control, and saving behavior based on socio-economic demographic factors of undergraduate students (S1) in NTT and to know the role of self-control as a mediator between the determinants and saving behavior. Using purposive sampling method, 321 respondent were taken from three universities. Data was collected using a questionnaire via google form, analyzed using SEM-PLS. The findings in the study show that most undergraduate students (S1) in NTT have high levels of financial literacy, family financial socialization, self-control, and saving behavior. Only peers are at a low level. In addition, self-control can be a mediator between financial literacy and socialization of family finances with the saving behavior of Undergraduate Students (S1) in NTT. Meanwhile, self-control cannot be a mediator between peers and saving behavior.